Arsenic in food chain through irrigation water-soil-crop pathway : risk assessment for sustainable agriculture of Bangladesh - Ahmed, Bashir (SLU/Dept. of Urban and Rural Development, 2009)
Elevated level of groundwater arsenic (As) in Bangladesh has resulted as a massive calamity of exposing a large population to health risk and affecting livelihood and sustainable development of the country. Natural sources are responsible this arsenic contamination and it has adverse impact from the local to regional level. The extensive use of arsenic contaminated groundwater in irrigation poses a potentially long term detrimental effect to human health as well as it is an environmental hazard. Numerous previous studies have emphasized on human As ingestion through drinking water. The current study focused on As ingested through the food chain. A detailed daily dietary intake survey was conducted using a Food Frequency Questionnaire (FFQ) to estimate the daily intake of As and thereby assess the risk of As contamination in groundwater for sustainable development of agriculture. This study was conducted in Matlab Upazila, south east Bangladesh, one of the hotspots for As contamination in groundwater. In ten irrigation wells water was sampled to establish the water chemistry and determine the total As concentration. This study observed that irrigation water contained 0.006 to 0.513 mg/L of total As. The agricultural soils of Matlab upazila have become highly contaminated with As due to the excessive use of As-rich groundwater (1.85 to 5.02 mg/kg). From the household survey, it was observed that daily water consumption by an adult ranged between 4 to 8 L. According to the AsMat field study the As concentration of most Matlab tube wells water contained more than 0.05 mg/L. Thereby, an adult is expected to have an intake 0.2 to 0.4 mg of As/day from drinking water. Concentrations of As in rice grain (with husk) from the As contaminated field were varied from 0.01 to 0.15 mg/kg. On the other hand, the rice grains (without husk) of study area contained below the detection limit of 0.02 mg/kg of As. According to the FFQ of this study it was found that the average daily rice consumption by an adult of this area was between 450 to 1020 g raw rice grains. In the present study, the average As concentrations in rice grain (without husk) were 0.02 mg/kg. With the consideration of this value, an adult of study area is expected 0.01 to 0.16 mg of As daily intake with rice. The concentration of As found in the present study is much lower than the permissible limit in rice (1.0 mg/kg) according to the WHO recommendation.